ANALISA PENGENDALIAN KUALITAS PRODUK ICE CREAM DENGAN METODE SIX SIGMA - Setia Bakti, Candra; Kartika, Hayu (Journal of Industrial Engineering & Management Research, 2020)
Abstract — Quality control activities at the company are purpose to ensure the production process that occurs on the company has been guiding limits and finding factors of product damage. Its expected to minimize product damage that could inflict a financial loss on the company. The food and beverage company that is the place where the authors conduct research is a company that produces ice cream. Currently, an obstacle faced by the company is the large number of a product defect that involves weight loss (gr per m2) not to meet the expected specifications. This matter is dominant in sweet corn ice cream products, which causes many products to be held. The filling process has made weight (grperm2) that not carry out the specification. The results obtained from the analysis with the method of Six Sigma (DMAIC) the filling process is obtained value of process capability (Cp), process capability index (Cpk), and sigma value respectively of 0.59, 0.32 and 2.43. The results are still below the ideal target, so the company must make process improvements. These improvements are carried out by ensuring the standard temperature and air pressure on the freezing machine and making the procedures more clear as the reference operator.